2007
DOI: 10.1177/0269215506071784
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of self-efficacy and rehabilitation among neurologically disabled adults

Abstract: Patients consistently identified 11 factors falling in the supraordinate themes of self, others and process, and these influenced their self-efficacy to participate in neurological rehabilitation. Patients consider rehabilitation in terms of either an 'adaptation' or 'recovery' model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 21 publications
6
55
0
2
Order By: Relevance
“…Future research is needed to investigate the experience of patients over time because the recovery process from stroke is dynamic and unstable. 55,56 Future research should also take into consideration the lived experience of caregivers since they have an important influence on stroke survivors. 57 Implications for practice …”
Section: Resultsmentioning
confidence: 99%
“…Future research is needed to investigate the experience of patients over time because the recovery process from stroke is dynamic and unstable. 55,56 Future research should also take into consideration the lived experience of caregivers since they have an important influence on stroke survivors. 57 Implications for practice …”
Section: Resultsmentioning
confidence: 99%
“…People with PD wanted to maintain their optimum function for as long as possible, manage symptoms, and slow further decline; these being recognised goals of neurorehabilitation [26,82]. People with stroke, in common with other studies [25,83,84], hoped to regain lost communication function to allow meaningful social participation.…”
Section: Communication Difficulties and Personal Recoverymentioning
confidence: 99%
“…Analyzing patient interviews, Pellat 10 found that patient involvement was key to the rehabilitation process. Dixon et al 11 exploring various constructs of self-efficacy in neurological rehabilitation, discovered several recurrent themes: self-reliance and independence. Furthermore, patients recognized the magnitude of willpower, making time to take an active role and working in partnership with the multidisciplinary team; being able to recognize for themselves that they were making progress and that they valued external reassurance on this from other patients, staff, and visitors.…”
Section: Review Of the Literaturementioning
confidence: 99%